Phytochemistry and Pharmacology of Callistemon viminalis (Myrtaceae): A Review - Ahmad, Kamal; Athar, Fareeda (Natural Products Journal, The, 2017)
Callistemon viminalis (weeping bottlebrush), belongs to the family Myrtaceae, is known to have medical importance. An ornamental plant stands for its numerous attributes such as antioxidant, moluscicidal, antibacterial, antifungal, allelopathic, anti-platelet aggregation, anti-quorum sensing, anti-infective, anti-helminthic and has also been found as an effective insecticidal activity. This plant possesses a wide range of secondary metabolites inclusive of triterpenoid, monoterpenes, steroid, steroida l glycoside, phenolic, tetra deca hydro xanthene diones, pyrrole derivatives, flavonoids and essential oils. An impression has been taken from previous research that the major constituents of C. viminalis are monoterpenes which are mainly responsible for different biological activities of C. viminalis. This review includes the information concerning the cultivation, morphology, microscopic studies, physiochemical, and phytochemistry, so as to exploit it further for the human welfare.
Keywords: phytochemistry